The Role of Quality Digital: The effect of WhatsApp business on consumer retention of MSMEs in Papua Mountains - Adi, Tiomy Butsianto; Karunia, Erick; Aswan, Aswan; Marsha, Deni; Azis, Muh. Irfandy; Febrian, Muhammad Rully; Syams, Tengku Putri Azizah (Amkop Management Accounting Review (AMAR), 2025)
This study aims to analyze the influence of WhatsApp Business on customer retention of MSMEs in the Papua Pegunungan region and to examine the moderating role of high-quality digital interaction in this relationship. The study is grounded in the context of infrastructure limitations in 3T (frontier, outermost, and disadvantaged) areas, which demand the use of practical and accessible digital communication media. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. Data were collected through a survey of 120 consumers who interact with local MSMEs via WhatsApp Business. The results indicate that WhatsApp Business has a positive and significant effect on customer retention. High-quality digital interaction also shows a considerable impact and moderates the relationship between WhatsApp Business and customer retention. The R² value of 0.576 demonstrates strong predictive power. This research contributes to the development of digital loyalty theory and provides practical implications for empowering MSMEs in disadvantaged regions to enhance digital communication in retaining customers.